Subacute onset leukodystrophy and visual-spatial disorders revealing phenylketonuria combined with homocysteinmia in adulthood: A case report. Issue 8 (February 2018) - Wang, Chunchen; Li, Jieying
Abstract: Rationale: Phenylketonuria (PKU) is a metabolic disorder, which manifests a progressive irreversible neurological impairment during infancy and childhood. Hyperhomocysteinemia also showed that it might be involved in pathophysiology of many neuropsychiatric disorders. The late-onset clinical manifestations of these 2 diseases have not been reported elsewhere. We speculated that the late-onset PKU is caused by 2 kinds of metabolic dysfunction synergistically, especially a short period of irregular diet directly caused clinical symptoms. Patient concerns: A 21-year old Asian male patient demonstrated subacute leukodystrophy and visual-spatial disorders of late onset in adulthood. Diagnoses: Phenylketonuria combined with homocysteinmia, who presented with heterozygous mutations in gene encoding PAH p.G247R (c.739G>C) and p.Y204C (c.611A>G), along with homozygous mutation of gene encoding MTHFR c.677C>T. Interventions: The patient was treated with cobalamine (500 μg/day), vitamin B6 (30 mg/day), folate (5 mg/day) and encouraged to follow a protein-restricted diet. Outcomes: Visual disorientation and cognitive function showed improvement. Head MR showed similar resolution with the original lesion. Serum homocysteine and folate analysis were normal with decreased phenylalanine level. Lessons: This case suggests that neurological involvement of progressive nervous system dysfunction could be caused by more than one kind of inherited metabolic disturbances, and each one can induce or deteriorate the manifestations of another metabolic disorders.